Pembelajaran Inovatif Abad 21 pada Materi Menggambar Denah Rumah Tinggal Menggunakan Program AutoCAD dengan Model Project Based Learning (PjBL) di SMK Negeri 1 Adiwerna Kabupaten Tegal - Teguh Priambudi (Cakrawala: Jurnal Pendidikan, 2022)
Low knowledge and skills in drawing floor plans with software using auocad programs greatly impact the value of students' knowledge and skills. This research aims to improve the knowledge and skills of drawing a home floor plan using an autocad program through the Project Based Learning strategy learning model. The study uses Project Based Learning, equipped with turorial videos, and the results of analytical studies of learning implementation plans. From the results of the study there was a change in the completion of student learning. This is also followed by an increase in the skills of students. Through project based learning strategies with the addition of video tutorials that are aired repeatedly greatly affect the results of student products. The resulting image product is close to perfect so that it affects the value of his skills.